A Comparison between Sustainability Frameworks: an Integrated Reading through ESG Criteria for Business Strategies and Enterprise Risk Management - Paola Casciotti (Fondazione Eni Enrico Mattei (FEEM), 2023)
Implementing the complex Agenda 2030, with its high global Sustainable Development Goals (SDGs) requires, in the by now short time horizon of reference, an extraordinary effort, at all institutionals and private levels, to converge effectively on the whole system of intermediate and interrelated targets. At the same time, it is highly strategic to ensure macro and microeconomic financial long term balances among public and private sectors. The role of Sustainable Finance, in this context, is absolutely central. On the legislative side, the evolution of international directives, from Non Financial Reporting to Sustainability Reporting, impose to pay attention to new criteria and contents, also in order to distinguish deviant greenwashing phenomena. The paper compares the main frameworks, concerning the multiple and complex dimensions of Sustainability, like the institutional ones (MDG, SDG, BES) and one of the most widespread standard of non financial reporting framework (GRI) adopted by companies. The study aims to identify suitable criteria to allow the development of a simplified integrated analysis model of all targets and indicators established and currently in use, in order to converge effectively on the SDGs, to implement coherent public and enterprise's policies and to produce realistic sustainability reports. The identified suitable criteria are the so called "ESG" criteria, increasingly recommended in the context of Sustainable Finance and by Supervisory bodies, as drivers in sustainability analyses, portfolio selection and rating determination. The paper, therefore, shows the results achieved by comparing these frameworks according to the proposed classification based on the individual E-S-G criteria and on their possible combinations (ES-EG-SG-ESG), through multidimensional matrixes of each goal, dimension, target and indicator (n.ê 855) of the examined frameworks. The analysis quantifies the importance of environmental, social and governance drivers and the importance of their combination for each framework considered and also through them altogether. As mentioned in this paper, further analysis by the author leads to develop, according to this ESG simplified classification approach, a new enterprise internal framework, to integrate both sustainability and financial drivers, into Corporates strategic investment decision models and internal capital allocation (tangible and intangible) policies. In this way, the integration of sustainability criteria in all enterprises' decision-making and risk management and control processes, becomes more effective and coherent with the Sustainable Development Goals. Consequently, the complex frameworks analysed, may become more easily comparable and integrated at an application enterprise level.
Keywords: F53; G390; L21; M14; O16; Q56; 330; ESG; SDGs; MDGs; GRI; Experimental Classification; Sustainable Finance; Integration; Enterprises; Corporate Risk Strategy; Sustainability Reporting; Sustainable Development